Who is Afraid of Asian FX Interventions? Large Lessons for Europe from a Three-asset-portfolio Model - Sebastian Dullien (Intervention. European Journal of Economics and Economic Policies, 2008)
The paper develops a three-asset-portfolio model to analyse consequences of foreign exchange market operations by Asian central banks on the exchange rates between euro, dollar and an Asian currency. It is found that - contrary to public belief - the purchase of dollar assets by Asian central banks strengthens the dollar against both the euro and the Asian currency. A diversification of Asian central bank reserves from dollar into euro would weaken the dollar against both other currencies. Thus, such a diversification would be incompatible with Asian currency pegs. However, it is shown that Asian central banks could alter their relative portfolio composition while keeping the peg intact if they shifted from intervening against the dollar into intervening against the euro.
Keywords: F31; 330; foreign exchange interventions; exchange rates; revived Bretton-Woods-System